Reclaiming Sacrifice Integrating Girardian and Feminist Insights on the Cross - King, Chelsea Jordan (Cham Springer International Publishing, 2024)
Chapter 1: Saved by an Innocent Death? -- Chapter 2: Feminist and Womanist Critiques of the Cross as Sacrifice -- Chapter 3: Girard and the Non-Sacrificial Reading of the Gospels.-Chapter 4: A Change of Heart -- Chapter 5: Reclaiming Sacrifice.
"This book brings René Girard’s mimetic theory into a carefully outlined dialogue with feminist theology regarding the difficult question of sacrifice. It convincingly shows how both approaches benefit from each other and how this synopsis leads to a much better understanding of sacrifice that no longer creates misunderstandings or supports the discrimination of women and people on the margins." —Wolfgang Palaver, Professor Emeritus at the Catholic Theological Faculty, University of Innsbruck "No question strikes more at the heart of Christian theology than the question of how Jesus’ death effects human salvation. Much discourse around this question either clings to old formulae and ignores the most neuralgic ethical challenges to sacrificial logic or misrepresents the main classical positions. By contrast, Chelsea Jordan King’s Reclaiming Sacrifice offers a needed intervention. She deftly brings together the most pressing insights of two contemporary discourses—Girardian and feminist / womanist—and holds them up against traditional theological understanding. What results is a masterly theological exposition that will greatly benefit both students and scholars. By doing so, King announces herself as an exciting new theological voice." —Dr. Grant Kaplan, Professor of Historical and Systematic Theology, Saint Louis University Many Christians profess that Jesus died as a sacrifice for sins. Why would God accept the murder of an innocent man as a sacrifice for sin? As important as this question is, there is a more fundamental question: What does it mean to say that Jesus dies as a sacrifice for sin? Within feminist theology, the very idea of sacrifice is laced with tension. Women and other marginalized groups have historically been oppressed by the use of the language of sacrifice. They have been told to live lives of self-sacrifice, at the expense of their well-being. Thus, many reject the language of sacrifice outright. Starting with an exploration of René Girard’s understanding of sacrifice, Chelsea Jordan King places Girard into direct dialogue with feminist theologians who raised similar critiques of violence. She then shows how we can re-claim the language of sacrifice in such a way that is liberative for all women and other marginalized groups. Chelsea Jordan King is an Assistant Professor in Catholic Studies at Sacred Heart University in Fairfield, Connecticut, USA. .
Keywords: Jésus-Christ - Crucifiement; Feminist Theology; Theology; Catholic Church; Sacrifice - Christianisme